A Narrative Review of the Published Literature, Hospital Practices, and Policies Related to External Ventricular Drains in the United States: The External Ventricular Drain Publications, Practices, and Policies (EVDPoP) Study. Issue 1 (27th January 2022) - Thamjamrassri, Thanyalak; Yuwapattanawong, Kornkamon; Chanthima, Phuriphong; Vavilala, Monica S.; Lele, Abhijit V.
Abstract : Supplemental Digital Content is available in the text. Abstract : External ventricular drain (EVD) placement and management pose risks to neurocritically ill patients. Yet, little is known about EVD management or hospital EVD management practices and policies in US hospitals. A narrative review was conducted to describe EVD-related publications reported in PubMed and Embase between 1953 and 2019, and a survey was used to examine US hospital EVD practices and policies, including adherence to EVD guideline recommendations. Overall, 912 relevant articles were published between 1953 and 2019 (average 21; range, 0 to 102 articles, per year), primarily related to indications for EVD placement (n=275, 30.2%), EVD-associated complications (n=206, 22.6%), and EVD care (n=200, 21.9%). The number of EVD publications increased over time ( R 2 =0.7), and most publications addressed EVD-associated infection (n=296, 73.4%) and EVD insertion (n=195, 45.2%). Survey responses were received from 30 hospitals (37.5% response rate), and reported use of antimicrobial-impregnated catheters in 80% of hospitals, preinsertion antibiotic administration in 70%, collection of cerebrospinal fluid samples for suspicion of ventriculitis in 73.3%, tracking of EVD-associated infection in 86.7%, routine EVD clamping during transport in 66.7%, and monitoring of intracranial pressure during transport in 33.3%. Adherence to hospital policies was high for recommendations related to flushing an EVD and changing cerebrospinal fluid drainage systems (100% [range, 0% to 100%] each), but low for intrahospital transportation (16.7% [0% to 83.3%]), EVD removal (0% [0% to 66.7%]), patient and family education (0% [0% to 100%]), and administration of intraventricular medication (0% [0% to 100%]). In summary, the published literature related to EVD insertion and maintenance, and reported EVD hospital practices and policies, primarily focus on reducing EVD-associated infections. Still, overall adherence of hospital EVD policies to guideline recommendations is modest. To promote a culture of EVD safety, clinicians should focus on reducing all EVD-associated adverse events.